The Effect of Ice Breaking Activities on Vocabulary Mastery Among EFL Students’ at SMA NU Palangka Raya - Alya Audria; Sabarun Sabarun; Zaitun Qamariah (Jurnal Pendidikan Indonesia, 2025)
Mastering vocabulary is indispensable for English as a Foreign Language (EFL) learners, as it underpins all language skills. However, many students continue to face difficulties in retaining and applying new vocabulary effectively. Prior studies have explored various strategies, yet few have examined the effect of engaging, student-centered techniques such as ice-breaking activities on vocabulary mastery among twelfth-grade EFL students at SMA NU Palangka Raya. Utilizing a quasi-experimental design, the researcher involved one experimental group and one control group, each undergoing pre-tests and post-tests to assess vocabulary mastery. The results showed that students in the experimental group demonstrated greater improvement than those in the control group, with post-test mean scores of 84.17 and 69.62, respectively (t(23) = 3.884, p < .001), indicating a statistically significant difference. These findings highlight the potential of ice-breaking activities to enhance vocabulary mastery by increasing student motivation, reducing anxiety, and encouraging active participation in learning. The study has important implications for educational practice, suggesting that ice-breaking activities should be integrated into regular EFL instruction as a pedagogical strategy rather than merely as warm-up exercises. Furthermore, these findings can inform teacher training programs and curriculum development policies aimed at creating more engaging and effective language learning environments in Indonesian secondary schools.